EVALUATING EXPULSION RATES: POSTPARTUM VERSUS INTERVAL INTRAUTERINE DEVICE INSERTION IN A TERTIARY CARE SETTING - KHUSHBOO SINGH; JAYA BARLA; VAISHALI KORDE NAYAK (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The intrauterine contraceptive device (IUCD) is a safe, reversible, feasible, and cheap form of contraception, yet its popularity is limited partly due to the risk of expulsion. Increased institutional deliveries can enhance family planning services, including postpartum IUCD (PPIUCD) insertion. This study compared the expulsion rates of PPIUCD and interval IUCD and aimed to educate, motivate, and counsel pregnant women about IUCD use. Methods: This was a comparative study conducted in a tertiary care teaching institute. After counseling, 900 women were willing for IUCD insertion. Outcomes were studied at 6 weeks and at 12 months. Results: A total of 4605 women were counseled regarding the benefits of IUCD, among which 900 women accepted IUCD as a method of contraception. Six hundred women accepted PPIUCD and 300 opted for interval IUCD. Among PPIUCD acceptors, 402 cases opted for intracesarean insertion of IUCD, and 198 cases opted for post-placental (n=114) and early postpartum (n=84) insertion of IUCD after vaginal delivery. The overall expulsion rate in the PPIUCD group was 6.16% and 1.66% in the interval IUCD group. The expulsion rate was more in multiparas than in primiparas. In the PPIUCD group, the patients who had IUCD insertion in the early postpartum period had a higher expulsion rate than the post-placental and intracesarean group. Conclusion: Proper counseling helps women make informed choices about IUCDs. Despite higher expulsion rates, PPIUCD can be recommended as an ideal method in developing countries like India, where women often do not return for contraceptive needs.